MODELISATION PAR LES ELEMENTS FINIS DE L'ADHESION ENTRE DEUX PLAQUES - HAMDI Mawloud (My University, 2012)
The objective of this memory of magister's was the numerical modeling by a finite element method the adhesive joint of two laminated composite plates using an epoxy adhesive. The commercial software ABAQUS was used for modeling. Several cases have been traited with include the effect of crack length and its angle orientation on the stresses and strains, the second case concerns the influence of the adhesive thickness on the stress states and deformations, the third is devoted to the influence of plate thickness on the J integral, stress and strain. The numerical results provided by the software Abaqus were then represented graphically both for the stress, strain, and the integral J. These results were compared with those in the literature.
Keywords: finite element, laminated composite plates, epoxy adhesive